Estrogen formulations and beauty care practices in Japanese women - Takeda T; Wong TF; Kitamura M; Yaegashi N (Dove Medical Press, 2012)
Takashi Takeda, Tze Fang Wong, Mari Kitamura, Nobuo YaegashiDepartment of Obstetrics and Gynecology, Tohoku University Graduate School of Medicine, Miyagi, JapanPurpose: Traditionally, oral estrogens have been used for hormone replacement therapy. However, in Japan, additional estrogen formulations have been used, including transdermal patches and transdermal gels. The latter have a unique commonality with cosmetics because both of them are applied to the skin. Beauty care is one of the most important lifestyle factors for women, and it has been reported that the amount of attention paid to beauty care has an effect in determining whether or not women will choose to undergo HRT during menopause. Therefore, our study focused on estrogen formulations and beauty care practices.Patients and methods: Fifty women who use hormone replacement therapy were recruited from the outpatient clinic of Tohoku University Hospital. They were treated with oral conjugated estrogen (n = 11), transdermal 17ß -estradiol patch (n = 11), and transdermal 17ß-estradiol gel (n = 28). They completed a questionnaire to assess their lifestyle (beauty care practices and exercise habits) and their compliance. The transdermal gel users were further interviewed about their subjective impressions regarding “smell”, “sticky feeling”, “spreadability”, and “irritation” on the skin using a five-grade scale.Results: There were no differences in the usability of medicines and patient compliance among the estrogen formulations. We observed a positive tendency between the level of beauty care and transdermal gel use (P = 0.0645, ordinary logistic regression analysis). The gel users placed top priority on a lack of “sticky feeling” but the subjective impression regarding “sticky feeling” was worst among the four factors (P < 0.01, Steel–Dwass test). Correspondence analysis showed that the subjective impressions of transdermal gel corresponding to usability in the range of “moderate” to “very good” and “sticky feeling” greatly affected the usability of the formulation.Conclusion: These results suggest that the level of attention to beauty care plays some role in the choice of estrogen formulations.Keywords: HRT, estrogen, transdermal gel, cosmetics, subjective impression